Могодын Хагарлаас Үүсэх Газар Хөдлөлийн Аюулыг Магадлалын Аргаар Үнэлэх нь - Т, Нарангарав; Ц, Баатарчулуун; Б, Ганбат (Scientific transaction of the National University of Mongolia. Physics, 2022)
Mongolia is considered to be located at the seismic active region and is divided into several tectonic zones. The Mogod earthquake (M=7.5, January 1967) which occurred at east of Hangai dome was one of the strongest earthquakes that occurred in the past century in Mongolia. The seismic event was closely studied by several researchers because seismicity of the Central Mongolian region was previously regarded as moderate.